Soil Biocrusts May Exert a Legacy Impact on the Rhizosphere Microbial Community of Plant Crops - Xiangbo Zou; Xinyu Jiang; Heng Jiang; Cheng Li; Jiong Cheng; Dongqing Ji; Jin Wang; Jiajin Ruan; Tiancheng Zhou; Cao Kuang; Ji Ye; Shiqin Yu (Agronomy)
Biological soil crusts (biocrusts) play important ecological roles in many ecosystems, but their legacy effects in subtropical agricultural systems are poorly understood. This study investigated how biocrusts impact soil properties and subsequent crop rhizosphere microbiomes. Soil with (+BC) and without (−BC) biocrusts was cultivated and used to grow pepper plants in a greenhouse experiment. Soil physicochemical properties and microbial communities in the pre-planting soils, and microbial communities in crop rhizosphere were analyzed. The results showed that soils with biocrust had significantly higher organic matter, total nitrogen, alkaline hydrolyzable nitrogen, total phosphorus, and total potassium content. Microbial community structures differed significantly among treatments, with −BC soils exhibiting higher microbial diversity in pre-planting conditions, while +BC soils showed higher diversity in crop rhizosphere soils. Soil properties, especially extractable potassium, total nitrogen, and organic matter content, were significantly correlated with rhizosphere microbial community structure. Additionally, our results showed that the first principal coordinate (PCoA1) of soil microbial community structure was significantly correlated with rhizosphere microbiota. Multiple regression analysis revealed that pre-planting soil microbial diversity indices and certain soil physicochemical properties could predict crop rhizosphere soil microbial diversity. Our results demonstrate that biocrusts can enhance soil fertility and alter microbial communities in subtropical agricultural soils, with persistent effects on the crop rhizosphere microbiome. This study provides new insights into the ecological legacy of biocrusts in managed subtropical ecosystems and their potential agricultural implications.